Fasting primes small intestinal regeneration after damage via a microbiome–metabolite–chromatin axis - Praveen Barrodia; Ajay Kumar Saw; Sabrina L. Jeter-Jones; Chia-Chi Chang; Jiansu Shao; Emre Arslan; Anand K. Singh; Suresh Satpati; Robert R. Jenq; Kunal Rai; Helen Piwnica-Worms (Proceedings of the National Academy of Sciences, 2026)
Fasting enhances small intestinal regeneration after radiation, but the contribution of the gut microbiome to this process remains uncharacterized. We identify Akkermansia muciniphila ( AKK ) as a key mediator of this response. AKK was enriched in fasted mice and its antibiotic depletion abrogated radioprotection, whereas reintroduction restored both organismal survival and intestinal integrity. Fasting elevated propionic acid, consistent with AKK ’s metabolic output. AKK -conditioned medium and propionate induced histone H3 acetylation in intestinal stem cell cultures while in vivo fasting induced AKK -dependent H3K27ac and H3K9ac, remodeling promoter–enhancer landscapes in crypt epithelial cells. Epigenetic profiling revealed a rewired core regulatory program enriched for pioneer transcription factors (Foxa, Gata, Klf), architectural organizers (Ctcf, Boris), and lineage-defining and metabolic regulators (Cdx2, Hnf4). This program supports expansion of a population of primed persister cells characterized by open chromatin accessibility at key stem and regenerative-associated loci including Clu , Olfm4 , Lgr5, Ascl2, Lrig1, Sox9, Rnf43, and Axin2. These findings define a fasting-induced microbiome–metabolite–chromatin axis that epigenetically primes highly plastic persister cells for rapid regeneration of the intestinal epithelium following radiation-induced injury.